Takayasu arteritis associated with autoimmune thyroiditis: A case report, clinical presentation, and treatment with monoclonal antibody - Qudsiya Ansari; Owais Ali; Praveen Unki; Surbhi Rathi (Indian Journal of Health Sciences and Biomedical Research KLEU, 2024)
Takayasu arteritis (TA), also known as “pulseless disease,” is a chronic large vessel vasculitis of unknown etiology that predominantly involves the aorta and its major branches. TA occurs worldwide and can affect all ethnic groups; the disease is most common in Asians. In this case report, we present a case of 15-year-old female, with a history of autoimmune thyroiditis presented with transient ischemic attack, the absence of peripheral and feeble central pulses with bruits that could be heard along the carotid, renal, and abdominal arteries, and a difference of > 10 mmHg in systolic blood pressure between arms. She was diagnosed clinically with TA. Digital subtraction angiography revealed aortoarteritis with involvement of bilateral subclavian, left proximal common carotid artery, and abdominal aorta. The patient was started on high-dose corticosteroid and methotrexate but due to steroid toxicity shifted to injection tocilizumab. She is on treatment and asymptomatic.